Chapter 21: Fighting a hard battle with a soft weapon: is international climate change law softening? - Kulovesi, Kati (Edward Elgar Publishing, 2023)
Is international climate change law softening? We take issue with the widely shared perception that the Paris Agreement constitutes a substantial step towards the softening of international climate change law, marking a shift from legally-binding climate change mitigation obligations under the Kyoto Protocol to a largely voluntary approach. We connect our analysis to literature on the 'softening' of international law more generally and find that both streams of literature reflect similar principled differences between arguments used by international lawyers and political scientists. Analysing views on hard and soft law in negotiations that took place under the UNFCCC in 2005-15 and culminated in the adoption of the Paris Agreement, we find no evidence of a principled preference in the international legal mindset towards soft law.